(Mis)representation of Nepali Culture in The Guru of Love - Kandel, Bhanu Bhakta Sharma (The Outlook: Journal of English Studies, 2020)
Samrat Upadhyay’s The Guru of Love has (mis)represented Nepali culture, society and thoughts from Western perspective. The writer has applied Western standards of life to represent Orient culture and society where he seems to have misguided somewhere. He has mentioned in the novel that Easterners have suffered from inferior thoughts and practices, the society has slavish mind-set regarding gender issues and sexual psychology, the society is poverty-stricken and it is full of the people with corrupt mind. The novel explains that females have been victimized from males’ domination practicing sexual violence, harassment and gender discrimination and dominance. Upadhayay has discussed about his birth place, cultures, society, language, religion, relatives, illicit sexual relation and political chaos which has helped to create a ‘discourse’ about Nepali society. The article argues how the novelist has (mis) represented the Nepai culture by discussing socio-cultural practices and it analyzes how it has tried to serve the palate of the Western readership.